XXI festival “Zodchesvo in Siberia 2021” - Grigoryeva, Elena (project baikal, 2021)
The Festival “Zodchestvo of Eastern Siberia” was founded at the turn of the millennium. The first Festival was held in 2001 at Irkutsk Sibexpocenter and caused a massive outcry among the architectural community in Siberia and throughout the country.Later the Festival “Zodchestvo of Eastern Siberia” became one of the most important annual architectural events in Russia. The first participants of the Festival were the architects from Eastern Siberia (such cities as Irkutsk, Angarsk, Bratsk, Chita and Krasnoyarsk, republics of Buryatia, Tyva, Khakassia, as well as Ust-Ordynsky and Aginsky national districts of Buryatia). Since 2007 architects from Western Siberia (Omsk and Barnaul) have also participated in the Festival. The Festival becomes open.The most topical issues are discussed at the Discussion Club of the Festival. Among the most prominent experts are A. Rappaport, O. Vendina, L. Kogan, A. Vysokovsky, A. Gimelstein, A.Kaftanov, M. Rozhansky, V. Dyatlov, A. Ivanov, D. Fesenko, A. Sirina, A. Finogenov. Prominent Russian architects give master classes, which enjoy great popularity. Thanks to the Festival, within twenty years, Siberian architects have met with masters from the capitals: Y. Gnedovsky, A. Asadov, S. Kiselev, A. Skokan, A. Bavykin, V. Plotkin, A. Savin, A. Cheltsov, A. Pavlova, S. Skuratov, N. Yavein, T. Kuzembaev, M. Mamoshin, Yu. Zemtsov, A. Bokov, T. Bashkaev, S. Gnedovsky, A. Chernikhov, V. Kuzmin, foreign architects M. Drahovsky, D. Dendra, G. Stanishev, as well as Siberian experts I. Popovsky, A. Myakota, P. Anisiforov, A. Dering and many other colleagues.The organizers consider the Festival to be a preparation stage for the International Festival “Zodchestvo” in Moscow. “Zodchestvo of Eastern Siberia” is traditionally held in Irkutsk. In 2014 it was first held in Krasnoyarsk, and in 2017 Krasnoyarsk housed the Festival for the second time. In the same year, Altai architects proposed to hold the next Festival in Barnaul. Thus, the Festival went beyond the borders of Eastern Siberia. We decided to maintain the name of the Festival, filling it with a new geographical meaning: “Zodchestvo in Siberia”. In 2018 the Festival was held in Barnaul, the capital of Altai, and in 2019 it was held in Tomsk. The twentieth-anniversary event took place on the native land, the city of Irkutsk. This year, Kemerovo celebrates the 300th anniversary of Kuzbass and hospitably hosts the Festival “Zodchestvo in Siberia 2021”.
Keywords: Zodchestvo in Siberia; festival; architecture